2015
DOI: 10.1590/s0034-8910.2015049005585
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dependence associated with health, social support, and lifestyle

Abstract: OBJECTIVE To analyze the prevalence of individuals at risk of dependence and its associated factors.METHODS The study was based on data from the Catalan Health Survey, Spain conducted in 2010 and 2011. Logistic regression models from a random sample of 3,842 individuals aged ≥ 15 years were used to classify individuals according to the state of their personal autonomy. Predictive models were proposed to identify indicators that helped distinguish dependent individuals from those at risk of dependence. Variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…Compared with the levels of family support, the levels of social support were more signi cant and negatively associated with dependency. The present results can be partly supported by previous ndings [18]. In some Asian countries, the elderly are highly respected in traditional societies and are living with close relatives [19].…”
Section: Discussionsupporting
confidence: 91%
“…Compared with the levels of family support, the levels of social support were more signi cant and negatively associated with dependency. The present results can be partly supported by previous ndings [18]. In some Asian countries, the elderly are highly respected in traditional societies and are living with close relatives [19].…”
Section: Discussionsupporting
confidence: 91%
“…Another key element for ensuring mental well-being is social support [10]. Such support is an essential determinant of an elderly person's health and functioning in their living environment [11,12]. Engagement in social activities and caring for grandchildren are additional elements that can be particularly beneficial for maintaining older people's health and subjective well-being [13,14].…”
Section: Mental Well-being Among Older Individualsmentioning
confidence: 99%
“…Based on the theoretical and empirical knowledge of the 7 themes, the following hypotheses were formulated: (a) perceived social support is positively associated with self-efficacy, 19 motivation, 20 and attitude, 21 which in turn is positively associated with information seeking, self-care, and stress management 22Y25 ; (b) social support is positively associated with information seeking, 26 self-care, 27 and stress management 28 ; and (c) information seeking is positively associated with self-care and stress management 29,30 ( Figure 1).…”
Section: Phase 2: Empirical Sectionmentioning
confidence: 99%
“…Previous studies have highlighted that social support is related to the promotion of psychological and physical well-being, such as reducing high stress levels in cancer patients 28 and decreasing death risk in chronic disease populations. 41 In addition, social support has been associated with a healthy lifestyle, 19 self-efficacy, 26 information-seeking behavior, 42 and motivation. 43 Our model showed that motivation and information-seeking behavior are significantly associated with self-care behaviors and stress management.…”
Section: Model Testing and Model Fitmentioning
confidence: 99%